1969
DOI: 10.1128/aem.18.6.977-984.1969
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nucleic Acid-Related Substances by Fermentative Processes. XXVIII. Accumulation of 5′ Inosinic Acid by a Manganese-Insensitive Mutant of Brevibacterium ammoniagenes

Abstract: A manganese-insensitive mutant, KY 13105, of Brevibacterium ammwniagenes which accumulates considerable amounts of 5' inosinic acid (IMP) in the presence of 100 to 1,000 Mg of Mn2+ per liter was obtained from an IMP-producing mutant of a manganese-sensitive strain, KY 13102. The effects of Mn2 at 0 to 30 pug/liter on IMP accumulation by KY 13105 were similar to those by KY 13102. However, the accumulation of IMP by KY 13105 was not affected by 100 to 1,000 ,Mg of MnS per liter, showing a clear difference from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…2, the cells accumulating IMP showed marked morphological changes. In IMP accumulation, it is known that hypoxanthine is first accumulated and then is followed by IMP accumulation which is accompanied by morphological changes (10). It thus appears that, under limitation of Mn2 , strain KY 13714 first accumulates inosine and thereafter excretes IMP into the medium without degrading it to inosine.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2, the cells accumulating IMP showed marked morphological changes. In IMP accumulation, it is known that hypoxanthine is first accumulated and then is followed by IMP accumulation which is accompanied by morphological changes (10). It thus appears that, under limitation of Mn2 , strain KY 13714 first accumulates inosine and thereafter excretes IMP into the medium without degrading it to inosine.…”
Section: Resultsmentioning
confidence: 99%
“…the parent strain (Table 3). We had also previously found that cellular morphology of the parent strain is severely affected by Mn2+ (8,10). Therefore, the morphological change resulting from various Mn2+ levels were examined in inosine accumulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations